The Human Capital Hoax: Work, Debt and Insecurity in the Era of Uberization - Fleming, Peter (Organization studies, 2017)
Human capital theory – developed by neoclassical economists like Gary Becker and Theodore Schultz – is widely considered a useful way to explain how employees might enhance their value in organizations, leading to improved skill, autonomy and socio-economic wellbeing. This essay argues the opposite. Human capital theory implies that employees should bear the costs (and benefits) of their investment. Highly individualized training and work practices are an inevitable corollary. Self-employment, portfolio careers, the ‘gig economy’ and on-demand business models (including Uber and Deliveroo) faithfully reflect the assumptions that inform human capital theory. I term this the radical responsibilization of the workforce and link it to growing economic insecurity, low productivity, diminished autonomy and worrying levels of personal debt. The essay concludes by proposing some possible solutions.